Capsule impairs efficient adherence of Streptococcus agalactiae to intestinal epithelium in tilapias Oreochromis sp. (November 2016) - Barato, P.; Martins, E.R.; Vasquez, G.M.; Ramirez, M.; Melo-Cristino, J.; Martínez, N.; Iregui, C.
Abstract: Streptococcosis caused by Streptococcus agalactiae is one of the most important diseases in the tilapia aquaculture industry. The role of the capsule of Streptococcus agalactiae in adherence to fish surfaces has not been evaluated and the mechanism of capsular regulation during adhesion has not been described. The aim of this study was to evaluate the role of the capsule of S. agalactiae during adhesion to intestinal epithelium of tilapia ( Oreochromis sp.) in an ex vivo infection model. We show that the capsule impairs the adhesion of bacteria to host intestinal epithelium. Wild type (WT) strain SaTiBe08-18 ( S. agalactiae recovered from tilapia) had reduced adhesion (P < 0.0001) in comparison with its unencapsulated mutant of SaTiBe08-18 (Δcps). When WT was treated with sterile saline solution (pH 5) before infection of intestine explants, the adhesion was reached. The results suggest that the capsule impairs the adhesion of S. agalactiae to tilapia intestine and that the acidic milieu could regulate adherence of encapsulated strains. We found GlcNAc on the surface of adherent Δcps but not over the capsule in WT. This difference could be explained by the GlcNAc composition of Lancefield group B antigen and the peptidoglycan in GBS (Group B Streptococcus) and also may be related with better exposure of glycosylated adhesins in unencapsulated fish GBS. Understanding capsular regulation during adhesion of S. agalactiae may provide new leads to find a successful anti-adherence therapy to prevent streptococcosis in tilapia.